A magnetic X-band frequency microwave nanoabsorbent made of iron oxide/halloysite nanostructures combined with polystyrene. Issue 10 (27th February 2023) - Jelodar, Diana Fallah; Rouhi, Mojtaba; Taheri-Ledari, Reza; Hajizadeh, Zoleikha; Maleki, Ali
Abstract : A magnetic hybrid nanoabsorbent made of iron oxide, halloysite and polystyrene is fabricated and utilized for the absorption of X-band microwaves. Abstract : A novel nanocomposite has been designed and fabricated through an in situ polymerization process, based on iron oxide nanoparticles (Fe3 O4 NPs), halloysite nanotubes (HNTs), and polystyrene (PS). The prepared nanocomposite (formulated as Fe3 O4 /HNT-PS) has been fully characterized through various methods, and its applicability in microwave absorption was investigated by using some single-layer and bilayer pellets containing nanocomposite and resin. The efficiency of the Fe3 O4 /HNT-PS composite with different weight ratios and pellets with the thickness of 3.0 and 4.0 mm were examined. Vector network analysis (VNA) revealed that the microwave (12 GHz) can be noticeably absorbed by Fe3 O4 /HNT-60% PS particles in a bilayer structure with 4.0 mm thickness and 85% resin of the pellets, resulting in a microwave absorption value of ca. −26.9 dB. The observed bandwidth (RL < −10 dB) was about 1.27 GHz, where ca. 95% of the radiated wave is absorbed. Ultimately, due to low-cost raw materials and high performance of the presented absorbent system, the Fe3 O4 /HNT-PS nanocomposite and the construction of the presented bilayer system can be subjected to further investigations to test and compare with other compounds for industrialization.